2020
DOI: 10.1016/j.jinf.2020.03.063
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged virus shedding even after seroconversion in a patient with COVID-19

Abstract: Coronavirus, uses the Angiotensin Converting Enzyme-2 Receptor to enter airway cells. Viral endocytosis is mediated by several factors, including clathrin, the adaptor protein-2 complex (AP2) and the adaptor-associated kinase-1 (AAK1). 2 According to a recent report, 3 COVID-19, the disease caused by SARS-CoV-2, is characterized by three clinical patterns: no symptoms, mild to moderate disease, severe pneumonia requiring admission to Intensive Care Unit (ICU) in up to 31% of the patients. 3 Thus far, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
281
1
12

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(305 citation statements)
references
References 8 publications
9
281
1
12
Order By: Relevance
“…Vero E6 cells have therefore already been used in studies with SARS-CoV and MERS-CoV ( 30 , 33 36 ) and also in the development of live-attenuated and inactivated vaccines for human use ( 37 , 38 ). More recently, they have been used in research into the viral infection mechanism in COVID-19 ( 23 , 39 , 40 ), the effects of the virus on cells, confirmation of viral infection ( 41 43 ) and pharmacological research ( 44 48 ).…”
Section: In Vitro Models ( Table 1 )mentioning
confidence: 99%
“…Vero E6 cells have therefore already been used in studies with SARS-CoV and MERS-CoV ( 30 , 33 36 ) and also in the development of live-attenuated and inactivated vaccines for human use ( 37 , 38 ). More recently, they have been used in research into the viral infection mechanism in COVID-19 ( 23 , 39 , 40 ), the effects of the virus on cells, confirmation of viral infection ( 41 43 ) and pharmacological research ( 44 48 ).…”
Section: In Vitro Models ( Table 1 )mentioning
confidence: 99%
“…Chirathaworn C et al 16 and individuals who traveled with COVID-19 cases had a high risk of infection [28]. Meanwhile, Guo et al showed that the median duration of antibody detection was 5 days for IgM and IgG and 14 days for IgG.…”
Section: Antibody Detection In Close Contacts Of Sars-cov-2 Patientsmentioning
confidence: 99%
“…Viral RNA has been shown to be detectable in recovered patients, although the duration of viral RNA shedding reported varied among infected patients. Viral RNA shedding can last at least 6 weeks [12][13][14][15][16]. Liu et al reported that patients with severe symptoms had a higher viral load and a longer viral shedding period than patients with mild symptoms (<10 days for the group with mild symptoms and >10 days for the group with severe symptoms).…”
Section: Introductionmentioning
confidence: 99%
“…Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) emerged in Wuhan, China, in late 2019, is now causing a pandemic COVID-19. It was estimated that 104-107 genome copies/ml were present in nasal and pharyngeal swab specimens from COVID-19 patients (Liu et al, 2020a). In a similar study, 104-105 genome copies /ml SARS-CoV2 were detectable in sputum from severe infected COVID 19 patients (Huang et al, 2020;Liu et al, 2020b).…”
Section: Discussionmentioning
confidence: 87%
“…Respiratory viruses are common in humans and are transmitted mostly via droplets or aerosols, or body secretions, such as tears, nasal or oral discharges. The amount of viruses shed in the nasal or oral secretion can range from 104 to 107 genome copies/ml depending on the severity of the infection and the types of viruses (Finberg et al, 2019;Liu et al, 2020a). For example, Middle East respiratory syndrome coronavirus (MERS-CoV) is a highly pathogenic coronavirus, can cause 34% mortality in infected humans (Ogimi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%